RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE WITH PREMARITAL SEXUAL BEHAVIOUR ON SMA N 7 SEMARANGSTUDENTS - Ilham Prayogo; Hastaning Sakti (Jurnal EMPATI, 2013)
Premarital sexual behavior is any behavior that is driven by sexual desire, both with the opposite sex or the same sex before marriage. Teenagers premarital sexual behavior can occur because of the attitude of teenagers who supports such behavior.Factors affecting the attitude itself one of them is emotional intelligence.This study aims to determine whether there is a relationship between emotional intelligence and attitudes toward premarital sexual behavior.The population in this study were 320 students of class XI SMA 7 Semarang.Sample was 167 students, which is obtained through cluster random sampling technique. Equipment collecting data in this study is the Scale Attitudes toward premarital sexual behavior 32 aitem (α = 0.935) and Emotional Intelligence Scale27 aitem (α = 0,849) who had been tested on 53 students of class XI SMA 7 Semarang.Simple regression analysis showed a correlation value of -0.268 and p = 0.000 (p <0.05), indicating that there is a significant relationship between emotional intelligence and attitudes toward premarital sexual behavior in high school students N 7 Semarang, that higher emotional intelligence will be followed Similarly, negative attitudes toward premarital sexual behavior and vice versa.Effective contribution of emotional intelligence to attitudes toward premarital sexual behavior is at 7.2%.These results indicate that there are other factors at 92.8% which is not revealed in this study.Distribution of the study sample showed 114 students in the category of high emotional intelligence with the empirical mean of 79.26 and the 114 students in the category of attitudes toward premarital sexual behavior is very low with the empirical mean of 54.04.